Perception Fishermen Community about the Importance of 12 Years of Formal Education - Permana, Bayu Indra; Mursidi, Agus (Universitas Malikussaleh, 2020)
This study aims to determine how people's perceptions fishermen about the importance of 12 years formal education and how the implications of the fishing community's perception of the importance of 12 years formal education. This research use desciptive qualitative approach. The sampling technique uses purposive sampling and snowball sampling and the data collection techniques used are documentation, semi-structured interviews and observation. Field data findings show that the fishing community in Kedungrejo Village is a heterogeneous, consumptive community and based on interviews found that community perceptions about the importance of 12 years of formal education are as a provision for diplomas to look for work as land laborers. The meaning of 12 years of formal education in the form of maturity has not yet been felt by the community from the number due to environmental and social factors which are seen from the number of 2292 elementary school students who continue to the first level only 30% ie 308 who reached the top education level. so the 12-year formal education function that has a role to develop the community's potential is indisputable because of the social stratum between the skipper fisherman and the fisherman laborers. It is here that the important function of 12 years formal education is completely collided with the perception of the fishing community in Kedungrejo Village, Muncar District.